Molecular descriptors suggest stapling as a strategy for optimizing membrane permeability of cyclic peptides - Li, Jianguo (2022)
Cyclic peptides represent a promising class of drug candidates. A significant obstacle limiting their development as therapeutics is the lack of an ability to predict their membrane permeability. We use molecular dynamics simulations to assess the ability of a set of widely used parameters in describing the membrane permeability of a set of model cyclic peptides; the parameters include polar surface area (PSA), the number of hydrogen bonds, and transfer free energy between an aqueous phase and a membrane mimicking phase. These parameters were found to generally correlate with the membrane permeability of the set of cyclic peptides. We propose two new descriptors, the charge reweighted PSA and the non-polar surface area to PSA ratio; both show enhanced correlation with membrane permeability. This inspired us to explore crosslinking of the peptide to reduce the accessible surface area of the backbone polar atoms, and we find that this can indeed result in reductions in the accessible PSA. This gives reason to speculate that crosslinking may result in increased permeability, thus suggesting a new scaffold for the development of cyclic peptides as potential therapeutics.